Network intervention analysis to assess the trajectory of change and intervention effects associated with the use of self-control training for ego depletion aftereffects - JunJi Ying; Xiaofang Zhang; Lei Ren; RiHan Wu; Wei Xiao; Xufeng Liu (BMC Psychology)
Abstract Purpose The purpose of this study was to use the advanced technique of Network Intervention Analysis (NIA) to investigate the trajectory of symptom change associated with the effects of self-control training on youth university students’ chronic ego depletion aftereffects. Methods The nine nodes of chronic ego depletion aftereffects and integrated self-control training were taken as nodes in the network and analyzed using NIA. Networks were computed at the baseline, at the end of treatment, at 1-, 3-, 6-, 9- and 12-month follow up. 62 samples were recruited from universities and randomly divided into two groups. The sample ranged in age from 18 to 25 years and included both males and females. Results Self-control training interventions directly improved the states of low self-efficacy, low adherence, and work burnout, as well as indirectly alleviated fatigue, emotional regulation disorders, and other issues. Follow-up surveys showed that the intervention not only had immediate effects but also had long-term effects. Conclusion These findings indicate that self-control training has a direct intervention effect on low self-efficacy, low adherence, and work burnout of youth university students’ ego depletion aftereffects. This study is the first application of NIA in abnormal psychological state intervention research outside the field of mental disorder treatment. NIA is a promising method to evaluate the trajectories of intervention change and the direct and indirect effects of training interventions. Clinical trial registration No. KY20202063-F-2; date of approval: 10th December, 2020.